2022
DOI: 10.2147/orr.s378278
|View full text |Cite
|
Sign up to set email alerts
|

Gunshot Wounds: Ballistics, Pathology, and Treatment Recommendations, with a Focus on Retained Bullets

Abstract: As the epidemic of gunshot injuries and firearm fatalities continues to proliferate in the United States, knowledge regarding gunshot wound (GSW) injury and management is increasingly relevant to health-care providers. Unfortunately, existing guidelines are largely outdated, written in a time that high-velocity weapons and deforming bullets were chiefly restricted to military use. Advances in firearm technology and increased accessibility of military grade firearms to civilians has exacerbated the nature of do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 197 publications
0
28
0
2
Order By: Relevance
“…The costing algorithm did not include health care costs such as personal services (eg, private physiotherapy), material costs (eg, property damage), second survivor costs (eg, witnesses experiencing psychological trauma), or other losses in societal goods and services. Our study reports nothing about police training, staffing, supervision, funding, ammunition, or firearm model . Our findings did not include data on ethnicity, immigration, criminal record, or whether the use of force was justified .…”
Section: Discussionmentioning
confidence: 80%
“…The costing algorithm did not include health care costs such as personal services (eg, private physiotherapy), material costs (eg, property damage), second survivor costs (eg, witnesses experiencing psychological trauma), or other losses in societal goods and services. Our study reports nothing about police training, staffing, supervision, funding, ammunition, or firearm model . Our findings did not include data on ethnicity, immigration, criminal record, or whether the use of force was justified .…”
Section: Discussionmentioning
confidence: 80%
“…A recent review by Baum et al [5] illustrates the effects of gunshot wounds and retained bullets and their management; the importance of identifying the type of gun, the caliber, and the trajectory within the body before planning surgical removal was highlighted [5][6][7]. Hollier et al, in a study based on 4 years of experience, mention that the severity of injury resulting from facial and neck gunshot wounds varies according to the caliber of the weapon used and to the distance from which the patient is shot [8].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review by Baum et al of the effects of gunshot wounds and retained bullets and their management, the importance of identifying the type of gun, the caliber, and the trajectory within the body before planning surgical removal was highlighted [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The ballistic analysis suggested that the bullet hit the garage door first and then penetrated the patient. In summary, ballistic injuries can be categorized as low-energy gunshot wounds [1]. Surgical removal was planned to prevent future bullet migration.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, irrigation and debridement are accepted as the first-line operative treatments. However, it may not result in better outcomes in most low-energy gunshot wounds of the extremities [1]. Whether to remove the bullet immediately in patients with intact neurological function also remains a dilemma.…”
Section: Introductionmentioning
confidence: 99%